Lower [18F]fallypride binding to dopamine D2/3 receptors in frontal brain areas in adults with 22q11.2 deletion syndrome: a positron emission tomography study. Issue 5 (2nd April 2020) - van Duin, Esther D. A.; Ceccarini, Jenny; Booij, Jan; Kasanova, Zuzana; Vingerhoets, Claudia; van Huijstee, Jytte; Heinzel, Alexander; Mohammadkhani-Shali, Siamak; Winz, Oliver; Mottaghy, Felix; Myin-Germeys, Inez; van Amelsvoort, Thérèse
Abstract: Background: The 22q11.2 deletion syndrome (22q11DS) is caused by a deletion on chromosome 22 locus q11.2. This copy number variant results in haplo-insufficiency of the catechol-O-methyltransferase (COMT) gene, and is associated with a significant increase in the risk for developing cognitive impairments and psychosis. The COMT gene encodes an enzyme that primarily modulates clearance of dopamine (DA) from the synaptic cleft, especially in the prefrontal cortical areas. Consequently, extracellular DA levels may be increased in prefrontal brain areas in 22q11DS, which may underlie the well-documented susceptibility for cognitive impairments and psychosis in affected individuals. This study aims to examine DA D2/3 receptor binding in frontal brain regions in adults with 22q11DS, as a proxy of frontal DA levels. Methods: The study was performed in 14 non-psychotic, relatively high functioning adults with 22q11DS and 16 age- and gender-matched healthy controls (HCs), who underwent DA D2/3 receptor [ 18 F]fallypride PET imaging. Frontal binding potential (BPND ) was used as the main outcome measure. Results: BPND was significantly lower in adults with 22q11DS compared with HCs in the prefrontal cortex and the anterior cingulate gyrus. After Bonferroni correction significance remained for the anterior cingulate gyrus. There were no between-group differences in BPND in the orbitofrontal cortex and anterior cingulate cortex. Conclusions: This study is the first to demonstrate lower frontal D2/3 receptor binding in adults with 22q11DS. It suggests that a 22q11.2 deletion affects frontal dopaminergic neurotransmission.